1
$\begingroup$

The Mean Value Theorem for Integrals is $\int_Sf(x)g(x)dx$ =$f(c)\int_Sg(x)dx$ I am asked to use this to prove the generalized MVT which is $$\frac{f'(c)}{g'(c)}=\frac{f(b)-f(a)}{g(b)-g(a)}$$

how can I link the integral MVT to the generalized MVT? I was thinking to use the FUndamental Calculus theorem which is F(x)=$\int_a^xf(t)dt$ and F'(x)=f(x).

$\endgroup$
1
$\begingroup$

Consider the function $h(x) = f(x)*(g(b) - g(a)) - g(x)*(f(b) - f(a))$ on $[a, b]$. Then: $$ h(a) = f(a)g(b) - f(a)g(a) - g(a)f(b) + g(a)f(a) = f(a)g(b) - f(b)g(a), $$ and $$ h(b) = f(b)*(g(b) - g(a)) - g(b)*(f(b) - f(a)) = f(a)g(b) - f(b)g(a). $$ We see that $h(a) = h(b)$, so by Rolle's theorem: there is a $c \in (a, b)$ such that $h'(c) = 0$. So: $$ f'(c)*(g(b) - g(a)) - g'(c)*(f(b) - f(a)) = 0 , $$ and we have: $$ \frac{f'(c)}{g'(c)} = \frac{f(b) - f(a)}{g(b) - g(a)}. $$

$\endgroup$
0
$\begingroup$

One approach is like this: $$\int_{a}^{b}f'(x)\,dx = \int_{a}^{b}\frac{f'(x)}{g'(x)}\cdot g'(x)\,dx = \frac{f'(c)}{g'(c)}\int_{a}^{b}g'(x)\,dx$$ so that $$\frac{f(b) - f(a)}{g(b) - g(a)} = \frac{f'(c)}{g'(c)}$$ The conditions required for mean value theorem of integrals is that both $f'(x),g'(x)$ are continuous and $g'(x) \neq 0$.

So this approach does establish the generalized mean value theorem also called by the name "Cauchy's MVT" but the above proof requires more conditions on $f, g$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.